The Development of Interactive Education Media to Improve Emotional Intelligence of Early Age Children in Raudhatul Athfal As-Syafiiyah - Hafsah; Edi Saputra; Suryaniar (Britain International for Academic Research (BIAR) Publisher, 2020)
This researcher discusses the development of interactive educational media to improve emotional intelligence of young children in Ra As-Syafiiyah. This research aims to produce test instruments to measure the ability to increase emotional intelligence of young children in Ra As-Syafiiyah. Valid, practical and effective. The type of research used is research and development (R&D), namely the development of interactive educational media. This interactive educational media development model was developed based on the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The test subjects in this study were students of class A and class B at the Ra As-Syafiiyah School. The output of this interactive education media is in the form of apk files that can be installed easily, making it easier for students in the learning process. Based on the results of limited trials conducted, the data obtained from the expert validation results with an average of 3.5 are in the category of very valid, because 3 ≤ M ≤ 4 so that the material on the media is said to be very valid, while the results of media expert validation with an average an average of 3.3 is in the very valid category, because 3 ≤ M ≤ 4 so interactive education media is said to be very valid. While the validation results of linguists with an average of 3 are in the very valid category, because 3 ≤ M ≤ 4 so interactive education media are said to be very valid. Effective because interactive education media is rated by students with positive responses with an average percentage of positive responses of students at 89.25% and average responses of 4.42 and teacher responses with an average response of 4.1 said to be effective because the percentage of student responses and teacher more than 50%. Practical because the results obtained from the learning media implementation of 89.28% are said to be practical because the percentage of interactive educational media implementation is greater than 70%.